2005
DOI: 10.1097/01.mpg.0000157914.40088.31
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms Associated with Orthostatic Intolerance

Abstract: Pediatric patients with chronic upper gastrointestinal symptoms may have underlying orthostatic intolerance. In patients with upper gastrointestinal symptoms and orthostatic intolerance, treatment of orthostatic intolerance may result in resolution of gastrointestinal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 28 publications
3
52
0
1
Order By: Relevance
“…Our results are consistent with those of Sullivan et al [4] in which 78% of pediatric patients with upper gastrointestinal symptoms (including abdominal pain and nausea) and OI experienced complete resolution of gastrointestinal symptoms when NMH or POTS was treated. A recent study suggested that the diagnostic criteria for OI/POTS in adults may be inadequate for children and that an increase in heart rate greater than 45 bpm may be a more appropriate cutoff to define POTS [5].…”
Section: Discussionsupporting
confidence: 95%
“…Our results are consistent with those of Sullivan et al [4] in which 78% of pediatric patients with upper gastrointestinal symptoms (including abdominal pain and nausea) and OI experienced complete resolution of gastrointestinal symptoms when NMH or POTS was treated. A recent study suggested that the diagnostic criteria for OI/POTS in adults may be inadequate for children and that an increase in heart rate greater than 45 bpm may be a more appropriate cutoff to define POTS [5].…”
Section: Discussionsupporting
confidence: 95%
“…Patients with orthostatic intolerance frequently have chronic GI complaints, most commonly abdominal pain, nausea, and vomiting. 30 However, the nausea often resolves with treatment of the orthostasis. Autonomic dysfunction can cause symptoms by altering either afferent or efferent pathways.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…A role for abnormal autonomic nervous system function is increasingly recognized which may not be limited to the gastrointestinal tract. In pediatrics, exploratory studies have found autonomic dysregulation in pediatric FGID [46]. FGID's have been associated with orthostatic intolerance (OI), mainly postural tachycardia syndrome (POTS) and syncope [4, 6], but other associations have not been carefully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In pediatrics, exploratory studies have found autonomic dysregulation in pediatric FGID [46]. FGID's have been associated with orthostatic intolerance (OI), mainly postural tachycardia syndrome (POTS) and syncope [4, 6], but other associations have not been carefully evaluated. Three main types of orthostatic disorders have been described in patients undergoing tilt table testing (TTT): postural tachycardia syndrome (POTS), reflex syncope, and orthostatic hypotension (OH).…”
Section: Introductionmentioning
confidence: 99%